Modulation of cGMP in Heart Failure: A New Therapeutic Paradigm - Boerrigter, Guido (2009)
Heart failure (HF) is a common disease that continues to be associated with high morbidity and mortality warranting novel therapeutic strategies. Cyclic guanosine monophosphate (cGMP) is the second messenger of several important signaling pathways based on distinct guanylate cyclases (GCs) in the cardiovascular system. Both the nitric oxide/soluble GC (NO/sGC) as well as the natriuretic peptide/GC-A (NP/GC-A) systems are disordered in HF, providing a rationale for their therapeutic augmentation. Soluble GC activation with conventional nitrovasodilators has been used for more than a century but is associated with cGMP-independent actions and the development of tolerance, actions which novel NO-independent sGC activators now in clinical development lack. Activation of GC-A by administration of naturally occurring or designer natriuretic peptides is an emerging field, as is the inhibition of enzymes that degrade endogenous NPs. Finally, inhibition of cGMP-degrading phosphodiesterases, particularly phosphodiesterase 5 provides an additional strategy to augment cGMP-signaling.